Genomic profiling and spatial SEIR modeling of COVID-19 transmission in Western New York - Bard, Jonathan E.; Jiang, Na; Emerson, Jamaal; Bartz, Madeleine; Lamb, Natalie A.; Marzullo, Brandon J.; Pohlman, Alyssa; Boccolucci, Amanda; Nowak, Norma J.; Yergeau, Donald A.; Crooks, Andrew T.; Surtees, Jennifer A. (Frontiers in Microbiology, 2024)
The COVID-19 pandemic has prompted an unprecedented global effort to understand and mitigate the spread of the SARS-CoV-2 virus. In this study, we present a comprehensive analysis of COVID-19 in Western New York (WNY), integrating individual patient-level genomic sequencing data with a spatially informed agent-based disease Susceptible-Exposed-Infectious-Recovered (SEIR) computational model. The integration of genomic and spatial data enables a multi-faceted exploration of the factors influencing the transmission patterns of COVID-19, including genetic variations in the viral genomes, population density, and movement dynamics in New York State (NYS). Our genomic analyses provide insights into the genetic heterogeneity of SARS-CoV-2 within a single lineage, at region-specific resolutions, while our population analyses provide models for SARS-CoV-2 lineage transmission. Together, our findings shed light on localized dynamics of the pandemic, revealing potential cross-county transmission networks. This interdisciplinary approach, bridging genomics and spatial modeling, contributes to a more comprehensive understanding of COVID-19 dynamics. The results of this study have implications for future public health strategies, including guiding targeted interventions and resource allocations to control the spread of similar viruses.